Water Recycle Project (WRP) / Idimazhar Idris @ Harun - Idris @ Harun, Idimazhar (Faculty of Mechanical Engineering, 2003)
“Water Recycle Project” (WRP) requires careful measure to ensure the project yield good benefit. Many parameters need to be investigated and studies done before the project could be carried out. This WRP involves the works of piping, wiring and the installation of pumps, motors, air regulations valves in order to make the project perfectly in progress. This is followed by the activity of testing, analysis and data collection and then from here the result will be obtained to identify the effectiveness of the project. At the same time the cost evaluation of the project will be done to know whether the project worthwhile or not. Even though the project is estimated to expend a lot of cost but with a better planning and precise measure, it is will sure, the project will be succeed and will be given a lot of profit.